IMPLEMENTASI VISI COSMOTHEANDRIC RAIMON PANIKKAR DALAM PENDIDIKAN ISLAM - Natsir, Ahmad (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2022)
This article aims to discuss Raimon Panikkar's religious theory, which he callsthe Cosmotheandric Vision. This theory is the result of Panikkar's experienceof navigating religious life. Then this theory is implemented in learningmanagement in the classroom. Therefore, Islamic education has always beendirected at the transmission of rigid dogmas, which have resulted a generationthat is less tolerant of differences. Meanwhile, at the same time, the seeking fora moderate learning model is still under debate and long discussion. This articleanswers at least two basic questions. First, how to explain the theory ofCosmotheandric Vision. This Cosmotheandric Vision emphasizes differencesas part of the difference in the universe. Although the universe has differentparts, all of them lead to one vision, complementing the others to get in harmonywith direction of universe. Second, how to implement the theory ofCosmotheandric Vision in Islamic education. Islamic education has basicallyintroduced the closing concept with the sentence “wallahu a'lam”. This sentenceis in line with Raimon Panikkar's cosmos view, which explains that the logoswill never be able to achieve God's truth (theos). The word “wallahu a'lam”has to be implemented in more depth regarding of truth the difference that theowner of truth is only One, Allah, while what educators teach is just a “belief”wich is far from the word “faith”.